Systematic Investigation of Algal Diversity of a Perennial Lake of Bamanwada Village, Chandrapur District, Maharashtra - Dr. B. Mallesh Reddy, (The Bioscan, 2025)
Inventory of biodiversity of each and every habitat is very essential to understand the species diversity and their exact distribution. A scientific investigation was carried out for a period of two consecutive years from 2020 to 2022 in order to enumerate the algal diversity of a perennial lake situated at Bamanwada village. During the study, a total of 64 taxa of phytoplanktons have been isolated from the lake. All the taxa isolated during the investigation have been properly identified and classified with the help of standard literature, and are presented here along with their microphotographs. Among the isolated taxa, two are the new reports for India, seven are new reports for the state and sixteen are reported first time from the district.